Role of social workers vs. farmers training in the context of Nepal - Tamang, Rajesh; Nepali, Som (Ridwan Institute, 2023)
Social work is widely considered one of the noblest professions which allow people to make significant changes to the society and is a worthy profession from humanitarian perspective. These individuals and groups have made significant impact across different areas but there are still many areas where social workers need to intervene in a more intensive as well as extensive way. Social service is one of the cornerstone and essential need of in the modern times to implement reforms, carry out utilitarian procedures and empower millions of marginalized groups and make them resourceful enough not just only manage their own lives but also to empower others and maintain the cycle of empowerment. Social workers can mediate in the agricultural process on two crucial levels- first it can familiarize the local people with the new technologies, available subsidies and facilities either by the state or by institutions and organizations, secondly, it can use the firsthand knowledge of the condition of the farmers to understand the need of the hour and convey the same to the policy makers. We have seen how many farmer’s agitations and movements have been successfully organized in our country on a large scale, but still two major lacunae in this whole process has limited the impact of these movements on a much greater scale- one, there is a dearth of larger social consciousness among the masses regarding the problem of farmers in general and these movements in specific. Social workers need to take this burden on their heads so as to ensure that not only the information is disseminated smoothly and effectively but also a larger audience can be built who not only can be aware of the condition of farmers but can also empathize with it, thus providing the base of mobilization of these groups for future causes.